Non-timber Amazonian Forest Products and Their Valuable Edible Nuts: Cutia Nut, Egg Nut, Sapucaia Nut and Brazil Nut - Lopes, Beatriz de Oliveira; Coelho, Caroline Correa de Souza; Souza, Aparecida das Graças Claret; Silva, Otniel Freitas- (Journal of Agricultural Studies, 2021)
The Amazon region contains the world’s leading genetic reserve of native plants, with most of the area located in Brazil. This region is rich in species that little known or still unknown by the population at large, including species that produce non-timber forest products (NTFPs) such as edible nuts. The objective was to verify the occurrence of these edible nuts in Brazil, to evaluate their potential and the possibility of other uses, in addition to expanding the knowledge about them. A bibliographic review of the last 50 years was carried out, mainly using the descriptors the popular name and the scientific name of the four nut trees present in the Amazon and their respective families, namely: agouti nut (Acioa edulis Prance) and egg nut (Acioa longipendula Pilg.) From the Chrysobalanaceae family, and sapucaia nut (Lecythis Pisonis Miers) and Brazil nut (Bertholletia excels Bonpl.) From the Lecythidaceae family. The Chrysobalanaceae has 450 species and 17 genera of woody plants and shrubs, producing oilseeds by some species, including egg and agouti nuts. The Lecythidaceae, on the other hand, has approximately 17 genera and 300 species, and in Brazil it is possible to find 9 genera and 122 species, 54 of them endemic, some of which produce edible seeds such as sapucaia and Brazil nuts. Those species have a great nutritional potential, and the chemical composition of their nuts reveals a good amount of lipids and proteins, but more in-depth research on the subject is necessary, including on other biases for better knowledge of the species, discovery of other potential uses and benefits and, consequently, their valorization.